Relevance of the Digital Marketing Course to the Needs of the World of Work in the Digital Business Study Program at Universitas Pendidikan Indonesia Tasikmalaya Campus - Alifya Arina Zahra,; Akmal, Fahril; Habibi, Fajar Moch.; Kusuma, Iqbal Jaya; Pratama, Rejas; Hafizhulmalik, Shiddiq; Nuryadin, Asep; Prehanto, Adi (International Conference on Digital Business Innovation and Technology Management (ICONBIT), 2024)
This research aims to analyze the relevance of the digital marketing course taught in the digital business study program Universitas Pendidikan Indonesia, Tasikmalaya Campus, to the needs of the modern world of work. In the era of the Industrial Revolution 4.0, digital marketing is an important skill that must be mastered by graduates because it supports the company's promotion strategy and market share expansion. This research used a descriptive quantitative method with data collection through survey to students and alumni to evaluate the extent to which the material taught was in accordance with the skills needed in the industry. The results of this study are expected to provide recommendations for curriculum improvement to be more relevant to technological developments and current industry trends, so as to improve graduate competence and competitiveness in the job market.